Are Risk Attitudes and Individualism Predictors of Entrepreneurship? A Multivariate Analysis of Romanian Data - Adrian Hatos; Roxana Hatos; Alina Bădulescu; Daniel Bădulescu (Amfiteatru Economic)
This paper emerges in the context of authors` previous investigations concerning the individual determinants of entrepreneurship. More specific, it focuses on elaborating and empirically testing hypotheses related to structural push and pull factors, e.g. age, gender, education, type of residence, and also to two kinds of psycho-attitudinal factors, i.e. risk aversion and individualist vs. etatist economic ideology. While the literature review gives credit to both hypotheses, especially for the influence of risk attitudes on starting a business, this paper focuses on the analysis of self-employment by using the block-model logistic regression on 2008 Romanian EVS (European Values Survey) data. The results of multivariate analysis confirm the importance of risk aversion for entrepreneurship, as expected, but reject the hypothesis of a significant effect of individual’s option for individualist vs. collectivist (or statist) continuum. It is important to notice that, contrary to expectations, two important push factors, i.e. age and education, do not correlate with self-employment and, on the other hand, risk attitude adds itself to the other effects without interacting with it. The theoretical consequences of the findings, the limits of the research and further developments are also discussed in the paper.